TESOL Teachers’ Resilience to Encounter Challenges and Explore Opportunities during COVID-19 Pandemic: A Case Study - Izzah, Navisatul; Febria, Desty (Elsya : Journal of English Language Studies, 2023)
The pandemic situation was not easy for teachers around the world. While they were forced to continue the learning process, many teachers did not get adequate support from the institutions such as the online learning platform and training related to the implementation of distance learning. There have been studies related to teachers’ resilience such as comparing teachers’ resilience in South Africa and United States, and factors affecting teachers’ resilience in Fiji, India and Malaysia. This study aims to explore teachers’ resilience in Indonesia to encounter challenges and take advantages from the opportunities that pandemic covid-19 offered. This study used a qualitative case study to explore this issue in depth. Three TESOL teachers from three different universities were invited to share about their experiences through semi-structured interview. The findings of this study revealed that TESOL teachers in Indonesia were resilient to teach the students even though there were many challenges such as internet connection issues and less supports from their institutions. The teachers facilitate their students with synchronous and asynchronous online classes. They also innovated their learning using applications such as Quizziz, Kahoot, Slido and Flipgrid. Furthermore, teachers were also resilient to explore opportunities offered by the pandemic-covid-19 such as developing their technology skills in using applications, video conferencing and social media use. . They also actively investigated emerging issues in pandemic covid-19 through conducting independent research. This research concluded that while the pandemic covid-19 brought some difficulties for teachers in Indonesia, teachers refused to give up on the situation, rather they were resilient, developed their skills, and explore the emerging opportunities offered.